2019
DOI: 10.1038/s41598-019-56229-w
|View full text |Cite
|
Sign up to set email alerts
|

Higuchi’s fractal dimension, but not frontal or posterior alpha asymmetry, predicts PID-5 anxiousness more than depressivity

Abstract: Depression is a major cause of health disability. EEG measures may provide one or more economical biomarkers for the diagnosis of depression. Here we compared frontal alpha asymmetry (FAA), posterior alpha asymmetry (PAA), and Higuchi’s fractal dimension (HFD) for their capacity to predict PID-5 depressivity and for the specificity of these predictions relative to PID-5 anxiousness. University students provided 8 or 10 minutes of resting EEG and PID-5 depressivity and PID-5 anxiousness questionnaire scores. FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 53 publications
1
4
0
2
Order By: Relevance
“… Shadli et al (2018) found no significant HFD differences between pre- and post-ketamine administration at any dosage. In contrary, we found significant differences in HFD at the lateral channels (F7 and F8) between anxiety patients and controls, consistent with our earlier findings ( Kawe et al, 2019 ). These results suggest that a shift from an anxious to a non-anxious state is related to a reduction in HFD at the lateral channels, corresponding to left and right prefrontal sites.…”
Section: Discussionsupporting
confidence: 93%
“… Shadli et al (2018) found no significant HFD differences between pre- and post-ketamine administration at any dosage. In contrary, we found significant differences in HFD at the lateral channels (F7 and F8) between anxiety patients and controls, consistent with our earlier findings ( Kawe et al, 2019 ). These results suggest that a shift from an anxious to a non-anxious state is related to a reduction in HFD at the lateral channels, corresponding to left and right prefrontal sites.…”
Section: Discussionsupporting
confidence: 93%
“…The dynamic marker HFD is the marker of the highest effectiveness and is expected to incorporate a maximal part of the information from the EEG signal. This conclusion is supported by many studies where HFD has been successfully used for the detection of small alterations in EEG related to different factors such as depression, anxiety, or microwave radiation 22,[37][38][39][40] . The traditional EEG band power marker ABP is the most commonly used band power marker which has shown good sensitivity in various applications 2,4,6,7 .…”
Section: Discussionunclassified
“…SM3. Software packages for physiological data analysis [ 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 ...…”
unclassified